Programmable yeasts for future food systems: A strain–function–application–safety framework - Qin Cao; Dongyuan Zhou; Ying Wang; Xiaoyang An; Long Ma; Shuli Man (Trends in Food Science & Technology, 2026)

Tailoring microstructure of coal-based hard carbon and electrochemical performance for sodium-ion battery anodes: Insights from the intrinsic properties of diverse coal precursors - Weibo Meng; Hui Guo; Baolin Xing; Qiaomiao Xu; Man Wang; Long Li; Huihui Zeng; Xiaoxiao Qu; Chuanxiang Zhang; Peng Li; Yijun Cao (Fuel, 2026)

CRISPR/Cas12a-driven miRNA-hypersensitive intelligent nanodrug release system for precision therapy of resistant triple-negative breast cancer - Weipan Peng; Mengting Shi; Bin Hu; Ying Yang; Hexin Qi; Xinru Liu; Jiajing Qiao; Shuli Man; Long Ma (Chemical Engineering Journal, 2026)

Riverine Li isotopes response to a flood event on the Chinese Loess Plateau - Jianqi Man; Long-Fei Gou; Zheng Chen; Wenqi Zhang; Jiayuan Ren; Zhiyuan Zhao; Chengfan Yang; Haoqiang Dong; Chenyuan Kang; Jun Xiao; Zhi-Qi Zhao; Zhenhong Li; et al. (Geochimica et Cosmochimica Acta, 2026)

Integrated microbiome and metabolomics analyses reveal gut-lung axis alteration following waterborne Pseudomonas aeruginosa exposure - Jingjing Bai; Jingyi Wen; Qin Cao; Menghan Pang; Long Ma; Shuli Man (Journal of Hazardous Materials, 2026)

Anchoring MoOx nanodots in N-doped porous carbon via a biomimetic strategy: enhanced supercapacitor performance - Li Li; Shou-Cheng Jiao; Chang-Wang Shao; Yu-Man Li; Long-Yu Zhang; Xing-Shun Cong; Xian-Yong Wei; Dan Mu (Fuel, 2026)

F–53B exacerbates doxorubicin-induced cardiotoxicity by impairing NRF2-dependent ferroptosis defense - Chaobo Yang; Jingbin Guo; Man Long; Haojing Liu; Jiewen Cai; Rongxin Zhang; Zhi Zeng; Yan Zhu; Haiqiong Liu (Chemico-Biological Interactions, 2026)

New ecdysteroids with anticomplementary activity from roots of Leuzea uniflora (L.) holub - Wen-qing Du; Can Liu; Ruo-mei Li; Ning-ning Shi; Yan-nan Ji; Jin-long Qi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

PfAgo-guided SERS signal conversion for amplification-free and semi-quantitative detection of Salmonella typhimurium in food and physiological samples - Ruibo Zhao; Jingjing Bai; Qiang Zhang; Jiayi Wei; Fei Deng; Myunghee Kim; Xingjie Li; Shuli Man; Weipan Peng; Long Ma (Journal of Hazardous Materials, 2026)

Deciphering EPS and microbial roles in nitrogen removal and sludge characteristics in AGS systems under different volume exchange ratios - Xinjie Xia; Yueqiao Wang; Yizhi Guo; Shuai Wang; Man Long; Jinsong Guo; Fang Fang (Journal of Environmental Sciences, 2026)

Multiplexed Thermus thermophilus Argonaute-triggered tri-color fluorescent palette biosensing for rapid detection and genotyping of Helicobacter pylori - Long Ma; Yajie Liu; Yongpo Mao; Jiayi Wang; Yiping Chen; Fei Deng; Zhiwei Zhu; Lanxiang Ou; Myunghee Kim; Shengying Ye; Weipan Peng; Shuli Man (Chemical Engineering Journal, 2026)

The impact of radiative cooling paint on a factory building in tropics - Di Han; Yongping Long; Man Pun Wan; Bing Feng Ng (Building and Environment, 2026)

Slope and grain size control on channel-levee development in mixed turbidite-contourite systems - Long He; Tao Jiang; Man Tang; Dongmei Tian; Licheng Cao; Cong Cheng (Marine Geology, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

Guided and programmable nuclease-based biosensing in food safety, quality, and authenticity detection: A comparative analysis of recent developments - Xinyue Li; Yongpo Mao; Yuhan Tian; Jiajing Qiao; Ruibo Zhao; Weipan Peng; Shuli Man; Zhixian Gao; Long Ma (Trends in Food Science & Technology, 2026)

Modulation of Glutamate Release by Dexmedetomidine Preserves Dendritic Spines and Alleviates Cognitive Impairment in a Murine Model of Perioperative Neurocognitive Disorder - Yan Zhang; Junzhao Li; Xueju Wang; Zhongyu Zhang; Shuai Long; Chuanyu Edward Li; Yan Liu; John Man Tak Chu; Raymond Chuen-Chung Chang; Gordon Tin-Chun Wong; Yong Zhang (Neuroscience Bulletin, 2026)
Perioperative neurocognitive disorders (PNDs) represent a significant challenge in the perioperative setting, while the pathophysiology of PNDs remains unclear. Utilizing a murine model of abdominal surgery, we found that abnormal glutamatergic neurotransmission in the medial prefrontal cortex (mPFC) and hippocampus contributes to postoperative cognitive impairments. Increases in the frequency of miniature excitatory postsynaptic currents in both the mPFC and CA1 neurons indicate enhanced presynaptic glutamate release while having little effect on inhibitory neurotransmission. Surgery also enhances glutamate release from presynaptic terminals in the Schaffer collateral pathway. In addition, abdominal surgery increased the activation of microglia and astrocytes, elevated central inflammatory markers, and reduced excitatory amino-acid transporter-2 expression. Dexmedetomidine significantly mitigates the postoperative cognitive deficits by reducing inflammation and preserving neuronal structural complexity and dendritic spine stability, likely through inhibiting glutamate release and enhancing its reuptake. These findings advance our understanding of the etiology of PNDs and provide hints for potential intervention.

ScCypA negatively regulates interferon antiviral response by targeting IRF3/7 in barbel chub (Squaliobarbus curriculus) - Lei Zhang; Hai-tai Chen; Man-Xuan Chen; Zhe Long; Shu-Ting Xiong; Tiao-Yi Xiao; Xiang Zhao (Aquaculture, 2026)

Petrology, geochemistry and geochronology of the Kekeya ash (SW Tarim Basin): Implications for its origin and provenance - Jia-Jun Mo; Yu-Ting Zhong; Man Wang; Le Zhang; Qiong Wu; Qiang Ma; He Wang; Jahandar Ramezani; Xiao-Long Huang; Fu-Yuan Wu; Yi-Gang Xu (Lithos, 2026)

Magnetic iron oxide-loaded coal-based activated carbon for Enhanced copper (II) removal: Batch and fluidized bed studies - Wen Fan; Bo Lv; Long Li; Yutong Jiao; Man Wang; Baolin Xing (Fuel, 2026)

A lyophilized paper-based platform integrating RT-RPA and CRISPR/Cas12a for smartphone-assisted point-of-care detection of norovirus in environmental and food samples - Lijuan Yin; Liangyuan Wang; Lu Yin; Lingzhi Yang; Baoxue Gao; Shuli Man; Fufeng Liu; Long Ma (Chemical Engineering Journal, 2026)

Tassel counting of individual ridge from UAV RGB imagery based on YOLOv8m with deep SORT and double-step Otsu thresholding algorithm by filtering abnormal IDs for maize breeding - Man Xia; Leilei He; Yu Gu; Xiaojuan Liu; Bryan Gilbert Murengami; Lamin L. Janneh; Rui Li; Yan Long; Anastasia Grecheneva; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Efficient removal of microplastics through a combined treatment process: Pre-filtration and adsorption - Bo Lv; Wen Fan; Long Li; Yutong Jiao; Man Wang; Baolin Xing (Journal of Environmental Management, 2025)

Dual mechanisms of pomelo peel extract in combating cough and lung injury: Inhibition of MAPK/NF-κB and restoration of gut microbiota - Piaoran Li; Jingjing Bai; Qiong Wu; Ning Zhang; Long Ma; Kai Chen; Shuli Man (Food Research International, 2025)

Silencing aquaporin 1 inhibits autophagy to exert anti-rheumatoid arthritis effects in TNF-α-induced fibroblast-like synoviocytes and adjuvant-induced arthritis rats - Man-yu Zhang; Meng-qing Wang; Yan Huang; Sheng-long Gu; Meng-yuan Zhou; Ze-shan Xu; Ling-ling Li; Min Lv; Li Cai; Rong Li (Inflammation Research, 2025)

Saponin-enriched tea tree essential oil nanoemulsion for extending the shelf life of Areca bananas - Long Phuoc Lieu; Le Minh Dat Nguyen; Thi Trinh To; Thi Khanh Van Pham; Ngoc Anh Luu; Gia Man Vu; Duc Tri Luu; Dinh Quan Nguyen (Biocatalysis and Agricultural Biotechnology, 2025)

Terpenoids from Alpinia galanga and their acetylcholinesterase inhibitory activity - Bo Zhou; Meng-Jia Guo; Xin-Man Zhao; Xiao-Long Li; Shao-Huan Liu; Xiang-Chun Shen; Nen-Ling Zhang (Natural Product Research, 2025)

Argonaute-triggered and enhancement-by-mixing nano-SERS-transduced triple cascade amplification strategy: Transforming ultrasensitive molecular detection of foodborne pathogenic bacteria - Minghui Lu; Xinyue Li; Jincan Liu; Yongpo Mao; Qiang Zhang; Shuli Man; Weipan Peng; Long Ma (Journal of Hazardous Materials, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

Isolation of two new isomers of fusarin D from Fusarium sp. G10, an endophytic fungus of Iris japonica - Ya-Nan An; An-Le Tan; Xiao-Ying Long; Yue Zhou; Man He; Xiao-Long Tang (Natural Product Research, 2025)

A site experiment on the effects of cool coating in a residential community under the tropical climate - Yong Ping Long; E. V. S. Kiran Kumar Donthu; Di Han; Man Di Zhou; Xiao Qin Zhang; Bing Feng Ng; Man Pun Wan (Sustainable Cities and Society, 2025)

Ultrasensitive, portable and multiplexed molecular detection of pathogenic bacteria in a cross-validating manner via Argonaute-triggered and reverse-phase enhanced fluorescent lateral flow bioassay - Xiaoqin Tang; Xinyue Li; Yuhan Tian; Qiang Zhang; Shuli Man; Weipan Peng; Long Ma (Journal of Hazardous Materials, 2025)

Temperature dependent evaporite-sourced Li isotopic seasonality in the upper Yellow River - Long-Fei Gou; Jiayuan Ren; Zheng Chen; Jianqi Man; Wenqi Zhang; Zhengjie Chen; Jun Xiao; Zhangdong Jin (Global and Planetary Change, 2025)

Alicycliphilus soli sp. nov., Isolated from a Plastic Film Greenhouse Soil and the Proposal for the Reclassification of Diaphorobacter limosus as Alicycliphilus limosus comb. nov. - Xinyu Liu; Hailong Liang; Yingying Liu; Huijun Zhang; Hui Han; Bingyue Xin; Xiaomin Wu; Feng Li; Man Song; Long Zhang (Current Microbiology, 2025)

Colloid phosphorus transport in agricultural soils: a critical review of content characteristics, migration mechanisms, and environmental drivers - Wen-Jing Liu; Man-Tong Luo; Rong-Liang Qiu; Ke-Tan Xie; Xin-Xian Long (Journal of Environmental Management, 2025)

Degrading hydrophilic PVC and hydrophobic PS microplastics by electrochemical oxidation technology: Comparation for BDD, PbO2, and DSA anodes - Xinyu Liu; Liwei Qiu; Youcun Bai; Xuzhong Zeng; Zhenzhen Zhao; Xinyi Long; Hebin Bao; Yue Zhao; Han Wang; Qun Yan; Shuaishuai Man (Journal of Environmental Chemical Engineering, 2025)

Effects of BRB on cyclic behavior of resilient RAC composite frames with ultra-high strength steel bars - Jianwei Zhang; Weiheng Liu; Man Zhang; Yuyang Long (Engineering Structures, 2025)

Butterfly-inspired structures on strong and tough metagel for enhanced passive radiative and evaporative cooling - Di Han; Jipeng Fei; Yongping Long; Yuanhang Yang; Anna Lushnikova; Hiba Mhiri; Christophe Ménézo; Man Pun Wan; Hong Li; Xuan Zhang; Bing Feng Ng (Chemical Engineering Journal, 2025)

Solasodine binds to glucocorticoid receptor to ameliorate airway remodeling and excessive autophagy in bronchial smooth muscle cells for allergic asthma - Zhen Guo; Jun-li Liu; Yan-ni Fang; Xiao-man Guo; Chun-long Ma; Jing-wei Wang (Toxicology and Applied Pharmacology, 2025)

Molecular mechanisms of andrographolide-induced kidney injury and senescence via SIRT3 inhibition - Yi Cai; Liduan Huang; Yanhong Hou; Peiwen Pang; Ying Zhou; Xuan Zhang; Yiyin Long; Huajian Li; Halimulati Muhetaer; Man Zhang; Bo Wu (Toxicology and Applied Pharmacology, 2025)

Potential of curdlan use on the improving textural, cooking and sensory quality, and predicted glycemic index of high-fiber pasta added with watermelon rind - Dien Quang Long; Thi Thu Tra Tran; Nu Minh Nguyet Ton; Van Viet Man Le (Bioactive Carbohydrates and Dietary Fibre, 2025)

Comprehensive wheat lodging detection under different UAV heights using machine/deep learning models - Jianing Long; Zhao Zhang; Qu Zhang; Xiaohui Zhao; C. Igathinathane; Jianfei Xing; Chayan Kumer Saha; Wenyi Sheng; Han Li; Man Zhang (Computers and Electronics in Agriculture, 2025)

Nitrogen removal adaptation and stability loss of anammox granular sludge under prolonged low-concentration PS-NPs and ciprofloxacin exposure - Shanshan Xu; Gonglei Wang; Zhiping Liu; Man Long; Jinsong Guo; Fang Fang (Journal of Environmental Chemical Engineering, 2025)

Chitinophaga defluvii sp. nov., a Cyhalofop-Butyl-Degrading Bacterium Isolated from Municipal Sludge - Xinyu Liu; Hailong Liang; Yumeng Zhu; Qian Zhou; Song Shao; Man Song; Huijun Zhang; Xiaomin Wu; Long Zhang (Current Microbiology, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

TBBPA caused multiple intestinal injuries via ROS/NF-κB signal in common carp - Man Qian; Yuan Geng; Jing-jing Wang; Hong-ru Wang; Ji-long Luo; Xue-jiao Gao (Aquatic Toxicology, 2025)

Calibration of the Solar X-ray Detector on-board the Macao Science Satellite-1B for Soft X-ray Detection - Man-Hei Ng; Xiaoping Zhang; Jianwu Chen; Yongqiang Shi; Fuchang Zuo; Wenxi Peng; Weichun Fu; Liansheng Li; Pengwei Luo; Chi-Long Tang; Guozheng Zhang; Zhiwu Mei; et al. (Science China Earth Sciences, 2025)

Recent advances of food safety detection by nucleic acid isothermal amplification integrated with CRISPR/Cas - Jiali Qiao; Zhiying Zhao; Yaru Li; Minghui Lu; Shuli Man; Shengying Ye; Qiang Zhang; Long Ma (Critical Reviews in Food Science and Nutrition, 2024)

Optimization of food-grade colloidal delivery systems for thermal processing applications: a review - Wen Xu; David Julian McClements; Xinwen Peng; Zhenlin Xu; Man Meng; Yidong Zou; Guanxiong Chen; Zhengyu Jin; Long Chen (Critical Reviews in Food Science and Nutrition, 2024)

Encapsulation of polyphenols in protein-based nanoparticles: Preparation, properties, and applications - Cuicui Li; Long Chen; David Julian McClements; Xinwen Peng; Zhenlin Xu; Man Meng; Hangyan Ji; Chao Qiu; Jie Long; Zhengyu Jin (Critical Reviews in Food Science and Nutrition, 2024)

Progress on molecular modification and functional applications of anthocyanins - Yun Wang; David Julian McClements; Long Chen; Xinwen Peng; Zhenlin Xu; Man Meng; Hangyan Ji; Chaohui Zhi; Lei Ye; Jianwei Zhao; Zhengyu Jin (Critical Reviews in Food Science and Nutrition, 2024)

Early postnatal and concurrent exposure to metals and neurobehavioral outcomes at 5 years: Associations with individual environmental exposures and mixtures - Sui-Ling Liao; Shen-Hao Lai; Yuan-Ting Hsu; Li-Chen Chen; Ming-Han Tsai; Man-Chin Hua; Tsung-Chieh Yao; Kuan-Wen Su; Kuo-Wei Yeh; Chih-Yung Chiu; Shau-Ku Huang; Jing-Long Huang (NeuroToxicology, 2024)

YTHDF2 phase separation promotes arsenic-induced keratinocyte transformation in a poly-m6A-dependent manner by inhibiting translational initiation of the key tumor suppressor PTEN - Tianhe Zhao; Wenxiao Xiong; Jingsilin Cai; Qian Zhang; Donglei Sun; Keyan Long; Jin Man; Zunzhen Zhang (Journal of Hazardous Materials, 2024)

Accelerating peroxymonosulfate activation over fiber-shaped Fe@Fe3C/CNF for ultrafast tetracyclines degradation: Active site synergy and mechanisms - Man Yang; Yafan Lu; Wenjuan Zhang; Long Xie; Junjie Tian; Yiliyasi Baikeli; Fang Wang; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Mika Sillanpää; Longlong Geng (Journal of Environmental Chemical Engineering, 2024)

High water resistance starch based intelligent label for the freshness monitoring of beverages - Yun Wang; David Julian McClements; Zipei Zhang; Ruojie Zhang; Kuang He; Ziqiang Lin; Xinwen Peng; Zhenlin Xu; Man Meng; Hangyan Ji; Jianwei Zhao; Zhengyu Jin; et al. (Food Chemistry, 2024)

Utilization of diverse probiotics to create human health promoting fatty acids: A review - Kuang He; Hao Cheng; David Julian McClements; Zhenlin Xu; Man Meng; Yidong Zou; Guanxiong Chen; Long Chen (Food Chemistry, 2024)

Preparation and characterization of calcium-binding starch and its application in microwaveable pre-fried foods - Xiangcun Wang; David Julian McClements; Zhenlin Xu; Man Meng; Chao Qiu; Jie Long; Zhengyu Jin; Long Chen (Food Hydrocolloids, 2024)

Potentially toxic element source apportionment and risk assessment in agricultural soils around a large-scale Pb-Zn mine in Southwest China - Heng Wei; Xuekui Niu; Minmin Li; Canwen Cui; Zhonghua Wei; Wei Long; Man Tang; Hong Yu; Peng Zhang; Liping He; Bo Pan (Journal of Environmental Chemical Engineering, 2024)

Insight into selenium biofortification and the selenite metabolic mechanism of Monascus ruber M7 - Lisha Zhu; Pengcheng Long; Man Hu; Liling Wang; Yanchun Shao; Shuiyuan Cheng; Xingxing Dong; Yi He (Food Chemistry, 2024)

Phytochemical and chemotaxonomic investigations on the fruit parts of Illicium verum Hook. f - Man Li; Pengcheng Yang; Mei Jin; Tieqiang Zong; Junnan Li; Sainan Li; Long Jin; Jinfeng Sun; Shengbao Diao; Wei Zhou; Gao Li (Biochemical Systematics and Ecology, 2024)

Experimental Study on Mechanical Behavior, Fracture Characteristics, and Acoustic Emission Damage Characteristics of Sandstone Under Triaxial Multistage Stress Disturbance - Sheng-Qi Yang; Jing Yang; Zong-Long Mu; Guang-Jian Liu; Man Huang; Ke-Sheng Li; Yan-Hua Huang (Rock Mechanics and Rock Engineering, 2024)

Monoterpene-chalcone conjugates and diarylheptanoids isolated from the seeds of Alpinia katsumadai Hayata with cytotoxic activity - Hua-Lin You; Bo Zhou; Meng-Jia Guo; Xin-Man Zhao; Xiao-Long Li; Xiang-Chun Shen; Nen-Ling Zhang (Phytochemistry, 2024)

Sample-in-answer-out centrifugal microfluidic chip reaction biosensor powered by Thermus thermophilus Argonaute (TtAgo) for rapid, highly sensitive and multiplexed molecular diagnostics of foodborne bacterial pathogens - Nan Wang; Qiang Zhang; Yajie Liu; Baoyan Huang; Shuli Man; Shengying Ye; Long Ma (Chemical Engineering Journal, 2024)

Starch-guest complexes interactions: Molecular mechanisms, effects on starch and functionality - Xiuping Liang; Long Chen; David Julian McClements; Jianwei Zhao; Xing Zhou; Chao Qiu; Jie Long; Hangyan Ji; Zhenlin Xu; Man Meng; Licheng Gao; Zhengyu Jin (Critical Reviews in Food Science and Nutrition, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Chronic Fluoride Exposure Induces Ovarian Dysfunction and Potential Association with Premature Ovarian Failure in Female Rats - Xiaoke Tang; Hongjuan Li; Yali Wang; Li Zeng; Ling Long; Yajun Qu; Hui Yang; Xiaolin Zhang; Yanmin Li; Yanni Yu; Qi Zhou; Man Luo (Biological Trace Element Research, 2024)

Recent progress in the hydrophobic modification of starch-based films - Ziqiang Lin; Hao Cheng; Kuang He; David Julian McClements; Zhengyu Jin; Zhenlin Xu; Man Meng; Xinwen Peng; Long Chen (Food Hydrocolloids, 2024)

Simulation advances with EnviBatE- A case study on urban heat island mitigation in Singapore - E.V.S. Kiran Kumar Donthu; Georgios-E Kyriakodis; Xiaoqin Zhang; Yong Ping Long; Man Pun Wan; Emmanuel Bozonnet (Building and Environment, 2024)

Characterization of two novel hydrolases from Sphingopyxis sp. DBS4 for enantioselective degradation of chiral herbicide diclofop-methyl - Zhenbo Mao; Man Song; Ruiqi Zhao; Yuan Liu; Yumeng Zhu; Xinyu Liu; Hailong Liang; Huijun Zhang; Xiaomin Wu; Guangli Wang; Feng Li; Long Zhang (Journal of Hazardous Materials, 2024)

Effect of phytic acid on the structure, properties and oil absorption of wheat flour - Yuanhui Chen; David Julian McClements; Kuang He; Xinwen Peng; Zhenlin Xu; Man Meng; Hangyan Ji; Jianwei Zhao; Zhengyu Jin; Long Chen (Food Hydrocolloids, 2024)

Pterostilbene binding to whey protein: Multi-spectroscopy and the antioxidant activity - Xiuping Liang; Long Chen; Zipei Zhang; Ruojie Zhang; David Julian McClements; Zhenlin Xu; Man Meng; Zhengyu Jin (Food Hydrocolloids, 2024)

Recent advances in the application of nanotechnology to create antioxidant active food packaging materials - Hao Cheng; Long Chen; David Julian McClements; Hao Xu; Jie Long; Jianwei Zhao; Zhenlin Xu; Man Meng; Zhengyu Jin (Critical Reviews in Food Science and Nutrition, 2024)

Investigation into the characteristics of bagasse processed with 3C-DES and the production of chemimechanical pulp for pulp molded - Yikui Zhu; Long Li; Yansu Hou; Chuan Xu; Guoxiang Hu; Yi Man; Vasilevich Sergey Vladimirovich; Jun Li; Qingang Xiong (Journal of Cleaner Production, 2024)

Dynamics of cool surface performance on urban microclimate: A full-scale experimental study in Singapore - E. V. S. Kiran Kumar Donthu; Yong Ping Long; Man Pun Wan; Mandi Zhou; Bing Feng Ng (Sustainable Cities and Society, 2024)

N6-methyladenosine promotes aberrant redox homeostasis required for arsenic carcinogenesis by controlling the adaptation of key antioxidant enzymes - Tianhe Zhao; Donglei Sun; Keyan Long; Wenxiao Xiong; Jin Man; Qian Zhang; Zunzhen Zhang (Journal of Hazardous Materials, 2024)

The repellent activities of plant ethanolic extracts and their derived compounds against three species of rice planthoppers and their potential side-effects on the main predator, Cyrtorhinus lividipennis - Jing Zhao; Ibrahim Maholidy Farid; Man Long; Karam Elgizawy; Zhihui Ren; Wanlun Cai; Weihua Ma; Hongxia Hua (Journal of Pest Science, 2024)

Oxidative Stress Induced by Arsenite is Involved in YTHDF2 Phase Separation - Jin Man; Qian Zhang; Tianhe Zhao; Donglei Sun; Weilian Sun; Keyan Long; Zunzhen Zhang (Biological Trace Element Research, 2024)

Starch as edible ink in 3D printing for food applications: a review - Yuanhui Chen; David Julian McClements; Xinwen Peng; Long Chen; Zhenlin Xu; Man Meng; Xing Zhou; Jianwei Zhao; Zhengyu Jin (Critical Reviews in Food Science and Nutrition, 2024)

Corrigendum to “Oral self-microemulsifying drug delivery system for honokiol's stress responses attenuation and anti-Cryptocaryon irritans efficacy enhancement in Trachinotus ovatus” [Aquaculture 578(15): 740130, 2024] - Yong-Can Zhou; Gui-Hua Li; Shao-Long Liu; Man-Yi Jiang; Zi-Chen Zhao; Heng-Wei Deng; Jian-Long Li; Dong-Dong Zhang; Wei-Liang Guo; Ji-Hui Huang (Aquaculture, 2024)

Oral self-microemulsifying drug delivery system for honokiol's stress responses attenuation and anti-Cryptocaryon irritans efficacy enhancement in Trachinotus ovatus - Yong-Can Zhou; Gui-Hua Li; Shao-Long Liu; Man-Yi Jiang; Zi-Chen Zhao; Heng-Wei Deng; Jian-Long Li; Dong-Dong Zhang; Wei-Liang Guo; Ji-Hui Huang (Aquaculture, 2024)

Bioactive delivery systems based on starch and its derivatives: Assembly and application at different structural levels - Xiuping Liang; Long Chen; David Julian McClements; Xinwen Peng; Zhenlin Xu; Man Meng; Zhengyu Jin (Food Chemistry, 2024)

Quaternary-ammonium chitosan, a promising packaging material in the food industry - Yu-Long Qiu; Yixi Li; Gong-Liang Zhang; Hongshun Hao; Hong-Man Hou; Jingran Bi (Carbohydrate Polymers, 2024)

Amino carboxymethyl chitosan//dialdehyde starch/polyvinyl alcohol double-layer film loaded with ε-polylysine - Xiaoxia Chen; Yixi Li; Yu-Long Qiu; Gong-Liang Zhang; Hongshun Hao; Hong-Man Hou; Jingran Bi (Food Chemistry, 2023)

A new exploration of the “Three Lines One Permit” policy: Marine zoning strategy based on land-sea coordination - Yingxian Long; Wen Zhou; Man Hong; Di Zhao; Ding Wen; Yuhuan Zhang; Xi Deng (Environmental Impact Assessment Review, 2023)

Exposure to epoxy-modified nanoplastics in the range of μg/L causes dysregulated intestinal permeability, reproductive capacity, and mitochondrial homeostasis by affecting antioxidant system in Caenorhabditis elegans - Man Qu; Yuhan An; Xinyi Jiang; Qinlin Wu; Long Miao; Xing Zhang; Yang Wang (Aquatic Toxicology, 2023)

A case study of a giant reactivated landslide based on NPR anchor cable Newton force early warning - Long-ji Guo; Zhi-gang Tao; Man-chao He; Jian-ning Liu; Massimo Coli (Journal of Mountain Science, 2023)

SKN-1/Nrf2-dependent regulation of mitochondrial homeostasis modulates transgenerational toxicity induced by nanoplastics with different surface charges in Caenorhabditis elegans - Man Qu; Long Miao; He Chen; Xing Zhang; Yang Wang (Journal of Hazardous Materials, 2023)

Gypenosides suppress hepatocellular carcinoma cells by blocking cholesterol biosynthesis through inhibition of MVA pathway enzyme HMGCS1 - Man-Yu Xiao; Fang-Fang Li; Peng Xie; Yan-Shuang Qi; Jin-Bo Xie; Wen-Jing Pei; Hao-Tian Luo; Mei Guo; Yu-Long Gu; Xiang-Lan Piao (Chemico-Biological Interactions, 2023)

The composition characteristics of endophytic communities and their relationship with metabolites profile in Ephedra sinica under wild and cultivated conditions - Hui Zhang; Ye Xia; Jin-Long Cui; Xin Ji; Shuang-Man Miao; Gang Zhang; Yi-Min Li (Environmental Science and Pollution Research, 2023)

Recent advances in the optimization of the sensory attributes of fried foods: Appearance, flavor, and texture - Xiangcun Wang; David Julian McClements; Zhenlin Xu; Man Meng; Chao Qiu; Jie Long; Zhengyu Jin; Long Chen (Trends in Food Science & Technology, 2023)

MSCs Ameliorate Hepatic IR Injury by Modulating Phenotypic Transformation of Kupffer Cells Through Drp-1 Dependent Mitochondrial Dynamics - Long-Cheng Shang; Man Wang; Yang Liu; Xinhua Zhu; Shuai Wang (Stem Cell Reviews and Reports, 2023)

N6-methyladenosine upregulates ribosome biogenesis in environmental carcinogenesis - Tianhe Zhao; Donglei Sun; Keyan Long; Bernardo Lemos; Qian Zhang; Jin Man; Manyu Zhao; Zunzhen Zhang (Science of The Total Environment, 2023)

Argonaute-triggered visual and rebuilding-free foodborne pathogenic bacteria detection - Yaru Li; Jun Kou; Xiao Han; Jiali Qiao; Wenlu Zhang; Shuli Man; Long Ma (Journal of Hazardous Materials, 2023)

Experimental and numerical investigations on the explosions nearby a free surface from both sides - Hao Tang; Zhao-Li Tian; Xin-Yang Ju; Ji-Tuan Feng; Yun-Long Liu; A-Man Zhang (Ocean Engineering, 2023)

A SERS-signalled, CRISPR/Cas-powered bioassay for amplification-free and anti-interference detection of SARS-CoV-2 in foods and environmental samples using a single tube-in-tube vessel - Long Ma; Wenlu Zhang; Lijuan Yin; Yaru Li; Jianwen Zhuang; Liang Shen; Shuli Man (Journal of Hazardous Materials, 2023)

Meta-analysis reveals cyanotoxins risk across African inland waters - Xu Zhao; Ying Liu; Yu-Ming Guo; Chi Xu; Liang Chen; Geoffrey A. Codd; Jun Chen; Ying Wang; Pu-Ze Wang; Li-Wei Yang; Long Zhou; Yan Li; et al. (Journal of Hazardous Materials, 2023)

Experimental and computational approaches to characterize a novel amidase that initiates the biodegradation of the herbicide propanil in Bosea sp. P5 - Long Zhang; Gui Yao; Zhenbo Mao; Man Song; Ruiqi Zhao; Xiaochun Zhang; Chun Chen; Huijun Zhang; Yuan Liu; Guangli Wang; Feng Li; Xiaomin Wu (Journal of Hazardous Materials, 2023)

Acute exposure to polystyrene nanoplastics inhibits the flocculation of activated sludge - Jianwei Qu; Hanxiang Li; Shanshan Xu; Jie Huang; Zhiping Liu; Man Long; Jinsong Guo; Fang Fang (Journal of Environmental Chemical Engineering, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Specific activation of cGAS-STING pathway by nanotherapeutics-mediated ferroptosis evoked endogenous signaling for boosting systemic tumor immunotherapy - Jun-Long Liang; Xiao-Kang Jin; Shi-Man Zhang; Qian-Xiao Huang; Ping Ji; Xin-Chen Deng; Si-Xue Cheng; Wei-Hai Chen; Xian-Zheng Zhang (Science Bulletin, 2023)

Fabrication of zein–carboxymethyl cellulose nanoparticles for co-delivery of quercetin and resveratrol - Zhongyu Yang; David Julian McClements; Xinwen Peng; Zhenlin Xu; Man Meng; Long Chen; Zhengyu Jin (Journal of Food Engineering, 2023)

A ratiometric fluorescent biosensing platform for ultrasensitive detection of Salmonella typhimurium via CRISPR/Cas12a and silver nanoclusters - Long Ma; Jiajing Wang; Yaru Li; Dan Liao; Wenlu Zhang; Xiao Han; Shuli Man (Journal of Hazardous Materials, 2023)

Research progresses on enzymatic modification of starch with 4-α-glucanotransferase - Yuanhui Chen; David Julian McClements; Xinwen Peng; Long Chen; Zhenlin Xu; Man Meng; Hangyan Ji; Jie Long; Chao Qiu; Jianwei Zhao; Zhengyu Jin (Trends in Food Science & Technology, 2023)

OsHLS1 regulates plant height and development by controlling active gibberellin accumulation in rice (Oryza sativa L.) - Tonghua Zhang; Jiafu Wang; Rui Luo; Jianmin Man; Qing Long; Ning Xu (Plant Science, 2023)

A new enantioselective dioxygenase for the (S)-enantiomer of the chiral herbicide dichlorprop in Sphingopyxis sp. DBS4 - Long Zhang; Man Song; Zhenbo Mao; Yuan Liu; Feng Li; Jiandong Jiang; Kai Chen (International Biodeterioration & Biodegradation, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

Structure and properties of flexible starch-based double network composite films induced by dopamine self-polymerization - Hao Xu; Long Chen; Zhenlin Xu; David Julian McClements; Hao Cheng; Chao Qiu; Jie Long; Hangyan Ji; Man Meng; Zhengyu Jin (Carbohydrate Polymers, 2023)

Combined Effects of Warming and Imidacloprid on Survival, Reproduction and Population Growth of Brachionus calyciflorus (Rotifera) - Ya Wen; Man-Man Cao; Zhi-Yu Huang; Yi-Long Xi (Bulletin of Environmental Contamination and Toxicology, 2022)

Damage and Failure Characteristics and Constitutive Model of Copper-Bearing Skarns Disturbed by Hierarchical Dynamic Loading After Loading And Unloading - Chun Wang; Jia Li; Lu- ping Cheng; Xin-ru Li; Pan-long Zhang; Man-gu Hu (Rock Mechanics and Rock Engineering, 2022)

Exploring the interaction relationship between Beautiful China-SciTech innovation using coupling coordination and predictive analysis: a case study of Zhejiang - Yi-di Hua; Ke-man Hu; Lu-yi Qiu; Hong-an Dong; Lei Ding; Sio-Long Lo (Environment, Development and Sustainability, 2022)

Identification and QTL mapping of important agronomic traits based on rice short-wide grain CSSL-Z752 with restorer line Xihui 18 as background - Lin-Jun Cai; Han Yun; Xiao-Long Zhong; Dan Du; Xi-Man Peng; Ji-Chao Dai; Zhen-Lin Yang; Fang-Ming Zhao; Chang-Wei Zhang (Cereal Research Communications, 2022)

Parkin Inhibits Static Mechanical Pain by Suppressing Membrane Trafficking of Mechano-transducing Ion Channel TACAN - Yi Lei; Man-Xiu Xie; Xian-Ying Cao; Xi Zhang; Yi-Bin Xiao; Xiao-Yu Tian; Yuan-Xin Zhu; Xiao-Long Zhang (Neuroscience Bulletin, 2022)

Sex-specific mediation of placental inflammatory biomarkers in the effects of prenatal phthalate coexposure on preschooler cognitive development - Hui Gao; Juan Tong; Bei-bei Zhu; Meng-long Geng; Hong Gan; Li Sun; Xiao-yan Wu; Kun Huang; Hui Cao; Wen-wen Liu; Shu-man Tao; Peng Ding; et al. (Environmental Science and Pollution Research, 2022)

Laser ablation inductively coupled plasma mass spectrometry analysis of Chinese lead-barium glass: combining multivariate kernel density estimation and maximum mean discrepancy to reinterpret the raw glass used for producing lead-barium glass - Qian Ma; Rui Wen; Yifan Yu; Long Wang; Man Li; Luwu Cai; Li Ping; Zhiqiang Zhao; Dong Wang; Xiang Wang; Ruoyu Shi; A. Mark Pollard (Archaeological and Anthropological Sciences, 2022)

Species and geographic specificity between endophytic fungi and host supported by parasitic Cynomorium songaricum and its host Nitraria tangutorum distributed in desert - Shuang-Man Miao; Yan-Yan Zhang; Jin-Long Cui; Gang Zhang (Archives of Microbiology, 2021)

Global patterns in leaf stoichiometry across coastal wetlands - Yu‐Kun Hu; Xu‐Yan Liu; Nian‐Peng He; Xu Pan; Song‐Yuan Long; Wei Li; Man‐Yin Zhang; Li‐Juan Cui (Global Ecology and Biogeography, 2021)
Aim Coastal wetlands provide crucial ecosystem functions and services, such as coastal protection, nutrient retention and C sequestration. Despite the important roles in global C, N and P cycling, the global variation in leaf stoichiometry across coastal wetlands remains unclear. Location Global. Time period 1980–2018. Major taxa studied Vascular plants. Methods By compiling a global dataset of 698 data records in 205 sites, we carried out systematic analyses of the world‐wide trends and their determinants of leaf element contents and ratios of plants across coastal wetlands. Results Leaf N and P contents increased significantly, but C:N, C:P and N:P ratios decreased with increasing latitude in coastal wetlands. The mean annual temperature was the predominant driver of leaf N, P and C:N, whereas soil N:P was a good predictor of leaf C:P and N:P ratios. Furthermore, N increased faster with P in plant leaves of coastal wetlands compared with terrestrial ecosystems. Within coastal wetlands, herb‐dominated salt marshes had a significantly higher leaf P content, lower leaf N:P ratio and lower scaling exponent of leaf N to P than tree‐dominated mangroves. Main conclusions The similar latitudinal patterns of leaf stoichiometry in coastal wetlands compared with terrestrial ecosystems reflected the similar influences of temperature. However, different slopes of leaf P and N:P ratios and N and P scaling relationships between these two ecosystems suggested that different salinity and tidal inundation levels result in different strategies of N and P use in coastal wetland plants. These differences in leaf stoichiometry between ecosystems and between different types of coastal wetlands might need to be emphasized in future biogeochemical modelling owing to their different roles in global nutrient and carbon cycling.

Differential relationship of fungal endophytic communities and metabolic profiling in the stems and roots of Ephedra sinica based on metagenomics and metabolomics - Qi Zhang; Xiao-Zan Xue; Shuang-Man Miao; Jin-Long Cui; Xue-Mei Qin (Symbiosis, 2020)

Component analysis and antiasthmatic effects of Huashanshen dripping pill - Shuli Man; Nina Cui; Xuanshuo Liu; Long Ma; Changxiao Liu; Wenyuan Gao (Medicinal Chemistry Research, 2020)

Dual Functions of Microglia in Ischemic Stroke - Chuan Qin; Luo-Qi Zhou; Xiao-Tong Ma; Zi-Wei Hu; Sheng Yang; Man Chen; Dale B. Bosco; Long-Jun Wu; Dai-Shi Tian (Neuroscience Bulletin, 2019)

Soil erosion of unpaved loess roads subjected to an extreme rainstorm event: a case study of the Jiuyuangou watershed on the Loess Plateau, China - Bo Yang; Wen-long Wang; Ming-ming Guo; Wen-zhao Guo; Wen-xin Wang; Hong-liang Kang; Man Zhao; Zhuo-xin Chen (Journal of Mountain Science, 2019)

Morphological analysis of the foramen magnum in finless porpoise (genus Neophocaena ) using postmortem computed tomography 3D volume rendered images - Brian Chin Wing Kot; Derek Kam Ping Chan; Adams Hei Long Yuen; Francis Ho Man Wong; Henry Chun Lok Tsui (Marine Mammal Science, 2019)

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

Low Serum Levels of Brain-Derived Neurotrophic Factor Were Associated with Poor Short-Term Functional Outcome and Mortality in Acute Ischemic Stroke - Jing Wang; Li Gao; Yan-Long Yang; Yu-Qian Li; Tao Chang; Ming-Hao Man; Xing-Ye Zhang; Shao-Chun Guo; Li-Hong Li (Molecular Neurobiology, 2017)

Landscape dynamics and driving forces of wetlands in the Tumen River Basin of China over the past 50 years - Xiao Jun Zheng; Peng Sun; Wei Hong Zhu; Zhen Xu; Jing Fu; Wei Dong Man; Hai Long Li; Jian Zhang; Lei Qin (Landscape and Ecological Engineering, 2017)

Canopy structure and light interception partitioning among shoots estimated from virtual trees: comparison between apple cultivars grown on different interstocks on the Chinese Loess Plateau - Wei-Wei Yang; Xi-Long Chen; Marc Saudreau; Xiao-Yun Zhang; Man-Rang Zhang; Hang-Kong Liu; Evelyne Costes; Ming-Yu Han (Trees, 2016)

Resting-state functional MR imaging shed insights into the brain of diabetes - Yun Fei Wang; Xue Man Ji; Guang Ming Lu; Long Jiang Zhang (Metabolic Brain Disease, 2016)

Cerebral blood flow changes in hemodialysis and peritoneal dialysis patients: an arterial-spin labeling MR imaging - Xiao Lu Jiang; Ji Qiu Wen; Long Jiang Zhang; Gang Zheng; Xue Li; Zhe Zhang; Ya Liu; Li Juan Zheng; Long Wu; Hui Juan Chen; Xiang Kong; Song Luo; et al. (Metabolic Brain Disease, 2016)

Procalcitonin Is a Stronger Predictor of Long-Term Functional Outcome and Mortality than High-Sensitivity C-Reactive Protein in Patients with Ischemic Stroke - Chao Wang; Li Gao; Zhi-Guo Zhang; Yu-Qian Li; Yan-Long Yang; Tao Chang; Long-Long Zheng; Xing-Ye Zhang; Ming-Hao Man; Li-Hong Li (Molecular Neurobiology, 2016)

Effects of coring directions on the mechanical properties of Chinese shale - Qiao Lyu; Ranjith PG; Xinping Long; Yong Kang; Man Huang (Arabian Journal of Geosciences, 2015)

Devosia honganensis sp. nov., isolated from the soil of a chemical factory - Long Zhang; Man Song; Xiao-Long Chen; Ren-Jie Xu; Kai Chen; Shun-Peng Li; Zhen-Yuan Xia; Jian-Dong Jiang (Antonie van Leeuwenhoek, 2015)

Ferrovibrio xuzhouensis sp. nov., a cyhalothrin-degrading bacterium isolated from cyhalothrin contaminated wastewater - Man Song; Long Zhang; Bin Sun; Hao Zhang; Hui Ding; Qiang Li; Suhui Guo; Xing Huang (Antonie van Leeuwenhoek, 2015)

Scoring the collective effects of SNPs: association of minor alleles with complex traits in model organisms - DeJian Yuan; ZuoBin Zhu; XiaoHua Tan; Jie Liang; Chen Zeng; JieGen Zhang; Jun Chen; Long Ma; Ayca Dogan; Gudrun Brockmann; Oliver Goldmann; Eva Medina; et al. (Science China Life Sciences, 2014)

Fluid Flow-Induced Calcium Response in Osteoclasts: Signaling Pathways - Ping Li; Chenglin Liu; Man Hu; Mian Long; Ding Zhang; Bo Huo (Annals of Biomedical Engineering, 2014)

Prognostic significance of microRNA-141 expression and its tumor suppressor function in human pancreatic ductal adenocarcinoma - Zi-Man Zhu; Yue-Fang Xu; Qin-Jun Su; Jun-Dong Du; Xiang-Long Tan; Yu-Liang Tu; Jing-Wang Tan; Hua-Bao Jiao (Molecular and Cellular Biochemistry, 2014)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

High prevalence of torque teno sus virus in China and genetic diversity of the 5’ non-coding region - Shao-Lun Zhai; Jin-Xue Long; Wen-Kang Wei; Qin-Ling Chen; Man-Lin Luo; Dian-Hong Lv; Da-Cheng Wu; Fei Gao; Shi-Shan Yuan; Guang-Zhi Tong; Zu-Zhang Wei (Archives of Virology, 2013)

RT-PCR test for detecting porcine sapovirus in weanling piglets in Hunan Province, China - Guo-Hua Liu; Run-Cheng Li; Ze-Bin Huang; Jun Yang; Chao-Ting Xiao; Jing Li; Man-Xiang Li; Yun-Qiu Yan; Xing-Long Yu (Tropical Animal Health and Production, 2012)

Fluid Flow-Induced Calcium Response in Early or Late Differentiated Osteoclasts - Ping Li; Man Hu; Shujin Sun; Yan Zhang; Yuxin Gao; Mian Long; Bo Huo; Ding Zhang (Annals of Biomedical Engineering, 2012)

Responses of phytoplankton diversity to physical disturbance under manual operation in a large reservoir, China - Zhe Li; Sheng Wang; Jinsong Guo; Fang Fang; Xu Gao; Man Long (Hydrobiologia, 2012)

Inhibitory Effect of Delphinidin on Monocyte–Endothelial Cell Adhesion Induced by Oxidized Low-Density Lipoprotein via ROS/p38MAPK/NF-κB Pathway - Chun-ye Chen; Long Yi; Xin Jin; Ting Zhang; Yu-jie Fu; Jun-dong Zhu; Man-tian Mi; Qian-yong Zhang; Wen-hua Ling; Bin Yu (Cell Biochemistry and Biophysics, 2011)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Activation of cloned BKCa channels in nitric oxide-induced apoptosis of HEK293 cells - Yu-Guang Ma; Ling Dong; Xiao-Long Ye; Chang-Lei Deng; Jiu-Hua Cheng; Wen-Chao Liu; Jin Ma; Yao-Ming Chang; Man-Jiang Xie (Apoptosis, 2010)

Syn-collisional transform faulting of the Tan-Lu fault zone, East China - Guang Zhu; Guo Sheng Liu; Man Lan Niu; Cheng Long Xie; Yong Sheng Wang; Biwei Xiang (International Journal of Earth Sciences, 2009)

Effects of rosiglitazone on native low-density-lipoprotein-induced respiratory burst in circulating monocytes and on the leukocyte–endothelial interaction in cholesterol-fed rats - Long Sheng Lu; Li Man Hung; Chang Hui Liao; Chau Chung Wu; Ming Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

Substrate preference of mycelium-bound lipase from a strain of Aspergillus Flavus Link - Kamariah Long; Hasanah M. Ghazali; Arbakariya Ariff; Yaakob Che Man; Christopher Bucke (Biotechnology Letters, 1998)